Cloud database in mobile augmented reality - Nurul Farahin Hikmatullah Darwisal; Ng, Giap Weng; Lee, Angeline Ling Sing (Springer, 2022)
Cloud computing is a technology that has been around since decades and have been used in many fields. This work is dedicated to design and implement Mobile Augmented Reality (MAR) with Cloud Database system. Certain articles are reviewed in order to reach the conclusions of this study, where the study’s focus is on the mobile storage requirements for MAR applications. It is destined to be an effectual solution to most developers, particularly (a) when a complex environment standing in the way for the majority of target users, also (b) in recognizing and handling a huge amount of data. That said, this work is first devoted to the question of what MAR is and how it can be identified. Next, it further clarified, elaborated, and compared to some related notions. As a result of building on these prior defining features and related notions, developers can flourish and leave their fingerprints on the future with their diverse powerful and engaging predictive models and explanatory models, in the context of use. Back as this work starts, MAR with a cloud data system is a challenging technology in touching target users’ life where they lived, daily.